2017
DOI: 10.1002/hep.29226
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Down‐Regulation Promotes β‐Oxidation to Fuel Hypertrophic Liver Growth After Hepatectomy in Mice

Abstract: PTEN down-regulation after hepatectomy promotes the burning of TRAS-derived lipids to fuel hypertrophic liver regeneration. Therefore, the anabolic function of PTEN deficiency in resting liver is transformed into catabolic activities upon tissue loss. These findings portray PTEN as a node coordinating liver growth with its energy demands and emphasize the need of lipids for regeneration. (Hepatology 2017;66:908-921).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 42 publications
2
56
0
Order By: Relevance
“…B,F). A recent study showed that PTEN coordinates liver growth with its energy demands and emphasizes the requisition of lipids for LR . We identify PDK4 as a key molecule coordinating hepatic lipid homeostasis with liver growth, but the role of PDK4 in the metabolism of extrahepatic tissues during LR needs to be identified.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…B,F). A recent study showed that PTEN coordinates liver growth with its energy demands and emphasizes the requisition of lipids for LR . We identify PDK4 as a key molecule coordinating hepatic lipid homeostasis with liver growth, but the role of PDK4 in the metabolism of extrahepatic tissues during LR needs to be identified.…”
Section: Discussionmentioning
confidence: 87%
“…). The TRAS is essential to LR, and FA uptake is an important element for TG storage . Hepatic FA metabolism is a tightly controlled process that is subjected to regulation at levels of uptake, oxidation, de novo synthesis, intracellular transport, and export to circulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, 1‐week survival (ie, the best measure for a functional liver recovery) appeared to be slightly compromised ( P = 0.09) after Yap1 knockdown and hepatectomy (Figure C), suggesting that the early promotion of liver weight gain (ie, up to 32 hours) through YAP1 is vital to regeneration after tissue loss. Finally, the macroscopic appearance of α Yap1 ‐siRNA‐treated liver was pale at 48 hours after sHx (Figure C), pointing to persisting steatosis that typifies liver remnants with a regenerative deficiency …”
Section: Resultsmentioning
confidence: 99%
“…To get better insight into the physiological role of YAP1 during liver regeneration, we examined its expression after extended hepatectomy (eHx). Liver failure after eHx develops due to deficient progression through the hepatocellular S‐ and M‐phases associated with a shutdown of pro‐proliferative pathways . If YAP1 indeed functions in the early cell cycle (including the S‐phase) but is dispensable for the M‐phase, its activity should be impaired at 32 hours, but not 48 hours, after eHx.…”
Section: Resultsmentioning
confidence: 99%